Harmoni dalam Kebhinekaan : Studi Fenomenologi dalam Malam Tirakatan di Kediri - Hanur, Binti Su’aidah; Janah, Uzlifatul; Winarsih, Sri (Proceedings of Annual Conference for Muslim Scholars, 2024)
Malam Tirakatan is a local tradition that not only remembers history, but also strengthens social and religious ties, and promotes the values of togetherness and tolerance in society. This tradition can serve as a platform for bringing people of different ethnicities, beliefs, and races together for a moment of unity. People from various ethnic and religious backgrounds gather to pray together for the progress of the village, nation and state, showing a form of tolerance between religious communities. This study used phenomenological studies in which this paper tries to investigate how interfaith prayer activities in Malam Tirakatan can be a symbol of tolerance and religious harmony in Indonesia especially in Kediri Residents. Through this practice, it is intended to the younger generation can better appreciate and preserve the cultural heritage of the ancestors.